2012
DOI: 10.1002/pmic.201200146
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic features of potential tumor suppressor NESG1 in nasopharyngeal carcinoma

Abstract: We previously defined the recently revised NESG1 gene as a potential tumor suppressor in nasopharyngeal carcinoma (NPC). Here, we further used proteomics technology to globally examine NESG1-controlled proteins in NPC cells. Twenty-six proteins were found to be deregulated by NESG1 using proteomics analysis while enolase 1 (alpha) (ENO1), heat shock protein 90 kDa beta (Grp94), member 1 (HSP90B1), and cathepsin D (CTSD) proteins were differentially expressed by Western blot. Interestingly, a-enolase (ENO1), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…This gene was cloned and revised by our team in 1999 and 2005 . We studied its functions, including proliferation, migration, invasion and related pathways in NPC cells, and defined it as a potential tumor suppressor . We also confirmed that NESG1 inhibited the pathogenesis of human nonsmall cell lung cancers (NSCLCs) …”
Section: Introductionmentioning
confidence: 72%
“…This gene was cloned and revised by our team in 1999 and 2005 . We studied its functions, including proliferation, migration, invasion and related pathways in NPC cells, and defined it as a potential tumor suppressor . We also confirmed that NESG1 inhibited the pathogenesis of human nonsmall cell lung cancers (NSCLCs) …”
Section: Introductionmentioning
confidence: 72%
“…Colony formation assay was analyzed according to a previous description [29]. Experiments were performed three times.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown genetic or epigenetic alterations in several CCDC genes in human cancers, including CCDC19 (NESG1) in nasopharyngeal carcinoma [7], CCDC62 …”
Section: Discussionmentioning
confidence: 99%
“…To date, more than 140 genes contain the coiled-coil domain, but their functions are unknown in many cases (http://www.genecards.org/). Previous studies have shown that approximately 40 CCDC genes are associated with diseases, including various metabolic diseases [4], cancers [5][6][7], mitochondrial disease [8], epigenetic disease [9] and heart disease [10]. The abnormal expression of CCDC containing proteins in nasopharyngeal carcinoma [7], prostate cancer [5], pancreatic cancer [6], gastric cancer [9], breast cancer [11] and colorectal cancer (CRC).…”
Section: Introductionmentioning
confidence: 99%